The conflict between strategic method application and theoretical knowledge in small and medium sized companies: the case of the Czech Republic - Sebestova, Jarmila (Business: Theory and Practice, 2016)
The purpose of the paper and presented research is to discover the potential conflict between often used managerial methods and the recommended methods for small businesses to find the gap between theory and practice in order to support cooperation between entrepreneurs and the university in the area of management education. The survey was conducted as a two phase project, in the first phase with 529 SMEs and with 214 SMEs in the second phase in the Czech Republic in 2012–2013 within the own research project. The main findings, presented in this paper focus on the conflict between practical knowledge, used in small businesses, when only 48.2% of companies in the first phase and 54.21% in the second phase used some of the methods commonly taught at university level such as controlling, benchmarking or TQM.